2002
DOI: 10.1128/aem.68.4.1919-1924.2002
|View full text |Cite
|
Sign up to set email alerts
|

Towards Growth of Arbuscular Mycorrhizal Fungi Independent of a Plant Host

Abstract: When surface-sterilized spores of the arbuscular mycorrhizal fungus (AMF) Glomus intraradices Sy167 were germinated on agar plates in the slightly modified minimum mineral medium described by G. Bécard and J. A. Fortin (New Phytol. 108:211-218, 1988), slime-forming bacteria, identified as Paenibacillus validus, frequently grew up. These bacteria were able to support growth of the fungus on the agar plates. In the presence of P. validus, hyphae branched profusely and formed coiled structures. These were much mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(65 citation statements)
references
References 30 publications
0
57
2
2
Order By: Relevance
“…Extracellular bacteria can affect fungal development and spore production, to the benefit or the detriment of the fungus. Bacteria stimulate spore germination in several fungi, including the plant-pathogenic oomycete Phytophthora alni (68), the saprophytic cheese-associated fungus Penicillium roqueforti (152), several bark beetle fungal symbionts (1), and the arbuscular mycorrhizal fungus Glomus intraradices Sy167 (161,162). Interestingly, antibiotic treatment to "cure" Rhizopus of the Burkholderia endobacteria living within its hyphae results in a fungus that no longer produces reproductive sporangia or spores (299).…”
Section: Consequences Of Bacterial-fungal Interactions For Participatmentioning
confidence: 99%
“…Extracellular bacteria can affect fungal development and spore production, to the benefit or the detriment of the fungus. Bacteria stimulate spore germination in several fungi, including the plant-pathogenic oomycete Phytophthora alni (68), the saprophytic cheese-associated fungus Penicillium roqueforti (152), several bark beetle fungal symbionts (1), and the arbuscular mycorrhizal fungus Glomus intraradices Sy167 (161,162). Interestingly, antibiotic treatment to "cure" Rhizopus of the Burkholderia endobacteria living within its hyphae results in a fungus that no longer produces reproductive sporangia or spores (299).…”
Section: Consequences Of Bacterial-fungal Interactions For Participatmentioning
confidence: 99%
“…flavonoids (AMF) and furans (ECM), that facilitate the growth of fungal hyphae and the subsequent colonization of plant roots by ECM (Founoune et al 2002;Duponnois and Plenchette 2003;Aspray et al 2006;Riedlinger et al 2006) and AM fungi (Duponnois and Plenchette 2003;Hildebrandt et al 2002Hildebrandt et al , 2006. Hildebrandt et al (2002Hildebrandt et al ( , 2006 have demonstrated that certain compounds (including raffinose and other unidentified metabolites) produced by strains of Paenibacillus can directly enhance the growth of AMF extraradical mycelium. Additionally, Kothamasi et al (2006) demonstrated that other species of bacteria, such as Pseudomonas aeruginosa, can solubilize important plant nutrients, especially phosphate, making them part of a group of bacteria called phosphate solubilizing bacteria (PSB).…”
Section: Mechanism 1: Biochar Changes Soil Nutrient Availabilitymentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) are obligate biotrophs that forms symbiotic or mutualistic association with roots of about 80% of plant species (Rai, 2001;Bianciotto et al, 2000;Hildebrandt et al, 2002;Cekic et al, 2012). The interaction between AMF and host plants under different conditions has received greater attention because of their mutual association (Miransari, 2009) especially when they are subjected to stresses.…”
Section: Amf and Stressmentioning
confidence: 99%